Nelson Mandela’s actions toward Adult Continuing Education as an example of what it can mean to be a dedicated life-long learner - Serge Gasore (Adult Education Research Conference, 2024)
In this presentation, one uses Nelson Mandela’s actions toward adult continuing education as an example of what it can mean to be a dedicated life-long learner.
Keywords: Life-long learner; Adult; Education